2014
DOI: 10.1093/mnras/stu110
|View full text |Cite
|
Sign up to set email alerts
|

New insights on accretion in supergiant fast X-ray transients from XMM–Newton and INTEGRAL observations of IGR J17544−2619

Abstract: XMM-Newton observations of the supergiant fast X-ray transient IGR J17544−2619 are reported and placed in the context of an analysis of archival INTEGRAL/IBIS data that provides a refined estimate of the orbital period at 4.9272±0.0004 days. A complete outburst history across the INTEGRAL mission is reported. Although the new XMM-Newton observations (each lasting ∼15 ks) targeted the peak flux in the phasefolded hard X-ray light curve of IGR J17544−2619, no bright outbursts were observed, the source spending t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 48 publications
2
31
1
Order By: Relevance
“…This confirms previous findings that most of the outbursts displayed by IGR J17544-2619 occur when the neutron star is closer to the supergiant companion and that the orbit of this system could be characterized by a non-negligible eccentricity (see, e.g., Drave et al 2014;Romano 2015, and references therein). Although this eccentricity could help in enhancing the X-ray dynamic range achievable by IGR J17544-2619, it cannot be the only explanation for the extreme behavior displayed by this source, as the system orbital period is relatively short and only a limited eccentricity of 0.2-0.3 can be expected (Walter et al 2015;Giménez-García et al 2016).…”
Section: Discussionsupporting
confidence: 91%
“…This confirms previous findings that most of the outbursts displayed by IGR J17544-2619 occur when the neutron star is closer to the supergiant companion and that the orbit of this system could be characterized by a non-negligible eccentricity (see, e.g., Drave et al 2014;Romano 2015, and references therein). Although this eccentricity could help in enhancing the X-ray dynamic range achievable by IGR J17544-2619, it cannot be the only explanation for the extreme behavior displayed by this source, as the system orbital period is relatively short and only a limited eccentricity of 0.2-0.3 can be expected (Walter et al 2015;Giménez-García et al 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Romano et al (2015) inspected Swift observations of the source experiencing an extraordinarily bright outburst (peak luminosity ∼10 38 erg/s), and reported the detection of X-ray pulsations with P spin = 11.60 s, also at a statistical significance of about 4σ. However, these results contrast with the analyses of XMM-Newton and NuSTAR observations performed by Drave et al (2014) and Bhalerao et al (2015) respectively. These authors do not find any evidence of pulsations for time scales of 1-2000 s.…”
Section: Igr J17544-2619contrasting
confidence: 96%
“…The companion star was spectroscopically identified by Pellizza et al (2006) (but see also Rahoui et al, 2008a) and the orbital period was measured at 4.92 days . A possible indication of pulsations from the direction of the source at 71 s was reported by Drave et al (2012) by using the RXTE/PCA, but then retracted (Drave et al, 2014). The deepest observation available was performed with the XIS on-board Suzaku (Rampy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…-IGR J17544-2619: Drave et al (2014) and Romano et al (2014a) observed that its X-ray luminosity varies mostly in the range 10 33−35 erg/s with some flares reaching few 10 36 erg/s. The source activity shows a clear peak at periastron, reminiscent of the building up of a tidal stream, and a minimum at apastron.…”
Section: Fast Transients Reaching Anomalously Low Luminositiesmentioning
confidence: 99%